Study of PLA-based Wood-Plastic Composites. Issue 1 (1st January 2023) - Li, Xiangrui; Yu, Jiaming; Meng, Lingyu; Li, Chunfeng; Liu, Mingli; Meng, Lipeng
Abstract: In order to cope with the environmental problems of plastic pollution and greenhouse gas emission, the development and utilization of environmentally friendly materials is urgent. Polylactic acid (PLA) is a completely degradable thermoplastic aliphatic polyester, but the high cost and poor toughness of PLA limit its wide application. PLA-based wood-plastic composites (WPC), prepared by laminating PLA with wood fibers, can reduce production costs and compensate for the deficiencies of PLA mechanical properties, while still retaining biodegradability. The synthesis of PLA, the preparation of PLA-based WPC, and the performance enhancement achieved by different wood fibers prepared WPC are presented. It is hoped that this will provide guidance for the early promotion of PLA-based WPCs.